Insertion of a Suicide Gene into an Immortalized Human Hepatocyte Cell Line - Naoya Kobayashi M.D., Ph.D.; Hirofumi Noguchi; Toshinori Totsugawa; Takamasa Watanabe; Toshihisa Matsumura; Toshiyoshi Fujiwara; Masahiro Miyazaki; Kenichi Fukaya; Masayoshi Namba; Noriaki Tanaka (Cell Transplantation, 2001)
For developing a bioartificial liver (BAL) device, an attractive alternative to the primary human hepatocytes would be the use of highly differentiated immortalized human hepatocytes with a safeguard. To test the feasibility, the primary human hepatocytes were immortalized by a plasmid SV3neo encoding simian virus 40 large T antigen (SV40Tag) gene. A highly differentiated hepatocyte line OUMS-29 was established. A suicide gene of herpes simplex virus-thymidine kinase (HSV-TK) was retrovirally introduced into OUMS-29 cells as a safeguard for clinical application. One of the resulting HSV-TK-positive cell lines, OUMS-29/ tk, grew in chemically defined serum-free medium with the gene expression of differentiated liver functions. OUMS-29/tk cells were 100 times more sensitive to ganciclovir compared with unmodified OUMS-29 cells in in vitro experiments. We have established a tightly regulated immortalized human hepatocyte cell line. Essentially unlimited availability of OUMS-29/tk cells may be clinically useful for BAL therapy.